Identification, taste characterization, and molecular docking study of a novel microbiota-derived umami peptide. (15th March 2023) - An, Feiyu; Cao, Kaixin; Ji, Shuaiqi; Wang, Yusheng; Pan, Guoyang; Ma, Yuanyuan; Zhao, Yue; Wu, Junrui; Wu, Rina
Highlights: A novel microbiota-derived umami and umami-enhancing peptide DFE was identified. DFE can help improve the overall taste of complex food systems. DFE binding to receptors was studied by molecular docking. DFE binds to T1R1/T1R3 through hydrogen bonding and electrostatic interactions. Abstract: Umami peptides are an important taste substance in fermented foods. However, in the absence of known microbiota-derived umami peptides, the understanding of the umami mechanism remains unclear. Tetragenococcus halophilus, a dominant fermentation bacteria, may be an important source of umami peptides. Accordingly, T. halophilus fermentation broth was fractioned by ethanol precipitation, gel chromatography, and reverse phase-high performance liquid chromatography. The isolated peptide fraction with the most intense umami taste was screened by amino acid composition and sensory analyses. Finally, three novel microbiota-derived peptides (DFE, LAGE, and QLQ) were identified, synthesized, and characterized for taste. Among them, only DFE had umami and umami-enhancing abilities improving multiple tastes. Molecular docking studies indicated that DEF binds to T1R1/T1R3 receptors through hydrogen bonding and electrostatic interactions involving receptor residues Ser332, Ser256, ASN41, His125, etc. This study highlights the critical role of microbiota-derived peptides in the umami taste of fermented foods.